Segregação Socioespacial em Sorocaba (1980 – 2018): o processo de territorialização nos condomínios Residencial Ipatinga e Parque dos Eucaliptos - Costa, Vinícius Felipe da (2019)
Based on the understanding that socio-spatial segregation occurs as a strategy for the real estate sector and for the State, preventing portions of the population from having access to decent housing, we sought to problematize the issue by analyzing the process of territorialization of groups of residents living in condominiums in a situation of land tenure irregularity in the western periphery of Sorocaba-SP. The cut of the Residencial Ipatinga and Parque dos Eucaliptos condominiums serves as an empirical basis to support this problem. For this, the historical process of housing financing and the periphery of housing in the city was analyzed in order to apprehend the production of socio-spatial segregation. Then it was verified how some social groups adapted or overcome this condition of exclusion. The practices present in these places reveal strategies for adapting to the conditions imposed by the hegemonic agents, constituting norms created locally, but which are connected to different scales and levels of reality. In this way, a theoretical exercise was carried out brought the global context of the place closer, exposing the nexus between the hegemonic use of the territory taken as a resource, and the hegemonized use of a territory built as a shelter.